2019
DOI: 10.1002/jnm.2640
|View full text |Cite
|
Sign up to set email alerts
|

An improved wideband equivalent circuit model for integrated spiral inductors in CMOS technology

Abstract: This paper presents an improved wideband single-π model for on-chip spiral inductors based on the independent tested ground PADs (ITGPs). For the ITGP, the input and output ground PADs are not connected together that introduces potential difference between the input and output ground PADs.However, the conventional inductor models are suitable for the ground PADs being connected together; they usually ignore the input and output potential difference and failed to achieve high model accuracy for the ITGP structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…With regard to NCGP, there is an electric coupling path between the input and the output grand pads since they are dependent on each other. Hence, R v , C g , R g are introduced to represent the parasitic parameters of the electric coupling path, 17 so the ground PADs at the Port A connects to the network A. Concerning SCGP and UCGP, the input and output ground have the same reference potential, the ground PADs at the Port A connects to net A.…”
Section: Principle Of the Fixed‐beam Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to NCGP, there is an electric coupling path between the input and the output grand pads since they are dependent on each other. Hence, R v , C g , R g are introduced to represent the parasitic parameters of the electric coupling path, 17 so the ground PADs at the Port A connects to the network A. Concerning SCGP and UCGP, the input and output ground have the same reference potential, the ground PADs at the Port A connects to net A.…”
Section: Principle Of the Fixed‐beam Propertymentioning
confidence: 99%
“…The Vector Network Analyzer is used to obtain two‐port S ‐parameters from 1 MHz to 67 GHz. The initial values of each elements of the equivalent circuit model are extracted by the equations from the paper Reference [17] and then the values of the elements are optimized. The extracted values are shown in Table 2 .…”
Section: Model Verificationmentioning
confidence: 99%
“…Although some high-frequency modeling methods of capacitors can be used to establish the models that reflect the multi-resonance characteristics of capacitors, there are still some problems, such as insufficient accuracy, low efficiency, and extreme complexity. 11 There are also some researches on the modeling of inductors and resistors, [12][13][14][15][16][17][18] but similarly, it is difficult to model the actual inductor in Figure 1(B), due to the lack of suitable equivalent circuit model form in these researches. Although some circuit model forms also produce multiple resonances, they are not suitable for modeling of single passive components in Figure 1 because their applicable objects are different or the impedance curve needed to be equivalent is simple.…”
Section: Introductionmentioning
confidence: 99%
“…Passive device models in CMOS technology are quite complicated due to the small area. Zhang et al presented an improved wideband single‐π model for on‐chip spiral inductors based on independent test ground PADs. A different group by Zhang et al reported a balun design algorithm based on compensation matching capacitors and their active S parameters.…”
mentioning
confidence: 99%